THE POWER SUPPLY SYSTEM AND CONTROL UNITS OF PLASMA NITRIDING - M. S. Ahmed (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
Switching power supply system and control units of ion plasma nitriding (IPN) is presented. Details of the construction method, hardware processing unit and merits of pulse mode of power supply are explained in the paper.